(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
For the correct legal classification of non-cash payments, it is important to identify non-cash settlement transactions carried out through credit institutions in accordance with the established procedure. The general rules of calculations are determined by the СС (Civil code). At the same time, non-cash settlements can also be regulated by banking regulations, in this regard, Non-cash settlements in this work are aimed at clarifying the concept and types of non-cash settlement operations.